Psychedelic-Assisted Therapies for Psychosocial Symptoms in Cancer: A Systematic Review and Meta-Analysis - Haley D. M. Schuman; Chantal Savard; Raèf Mina; Sofia Barkova; Hanna S. W. Conradi; Julie M. Deleemans; Linda E. Carlson (Current Oncology, 2025)
This systematic review and meta-analysis evaluates (1) the effectiveness of psychedelic-assisted therapy (PAT) using psilocybin and ketamine for psychosocial symptoms in adults with cancer, (2) contextualizes findings with non-randomized and exploratory studies of other psychedelics, and (3) examines the role of therapeutic frameworks in shaping outcomes. We searched PubMed, Cochrane Library, PsycINFO, and EMBASE (2000–2024) for randomized controlled trials (RCTs) and non-randomized studies investigating psychedelic agents in cancer populations. Meta-analyses pooled RCTs of psilocybin or ketamine using random-effects models. Non-randomized studies were synthesized narratively. Risk of bias and evidence certainty were assessed via Cochrane ROB 2.0, NIH Before–After tool, and GRADE. Eleven placebo-controlled RCTs and four single open-label studies were included. Meta-analysis of four ketamine RCTs (n = 354) showed large, rapid effects on depression/anxiety (Hedges’ g = −1.37, 95% CI: −2.66 to −0.08; I2 = 92%). Three psilocybin RCTs (n = 101) showed a large effect of psilocybin on alleviating depression (Hedges’ g = −3.13, 95% CI: −10.04 to 3.77; I2 = 95%). MDMA and LSD trials suggested promise but lacked rigor. PAT may offer meaningful relief for cancer-related distress, though effects vary by therapeutic model and context. Oncology-specific trials are needed to standardize and scale for implementation.